Improving Students’ Movement Activeness through Game Modification in Junior High School Badminton Training - ghon lisdiantoro; Agung Dwi Darmawan; Ardyansyah Arief Budi Utomo (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
Badminton extracurriculars always provide opportunities for students to be directly involved in various learning experiences through activities and games that are carried out in a systematic, planned and directed manner. When there is an improvement in fitness and skills in each school as a continuation of the badminton training subjects, students become good, in this case the teacher when providing material provides creativity and innovation so that it is easier to be accepted, understood and practiced by every student. Determining modifications or choosing strategies for learning activity needs to consider, tools, and time based on student characteristics. Badminton extracurricular training requires modifications because an extracurricular coach explains several aspects related to modifications so that the training can run actively, efficiently and effectively. The purpose of this study is to determine the effect of game modification on student activity in badminton training at SMP 4 Madiun City. In this study, the researcher used the following research methods with the type of pseudo-experiment through a quantitative approach, as well as the design used by One Group pre-test-post-test, the number of samples used was 22 students. Data was collected using the Focus Proportion Analysis (APF) instrument. In the calculation value of Pre-Test ATA is 62.5% and SDE is 45% while for the calculation value of Post-test ATA is 67.5% and SDE is 50.7% which means that there is a difference in the calculation value of ATA 5% and SDE 5.7% and the percentage increase in pre-test and post-test is 11.8%. Meanwhile, from the analysis of the T test, namely Tcount or sig (0.00) < Ttable (0.05) which means that there is an effect of game modification on student activity in badminton training at SMP 4 Madiun City. So it was concluded that there was a significant influence on the activeness of students' movements before and after the application of game modification. It can be said that by providing game modifications, it can have a significant influence on student activeness in badminton training at SMP 4 Madiun City.